(untitled) - Kamien, Roger (Boston, Mass., 2006)
Whether from a concert stage or at the front of a classroom, Roger Kamien knows how to reach an audience--blending intelligence and passion to lift music from the page and bring it to life. His unique combination of artistic and teaching skills makes Music: An Appreciation, Brief Edition an invaluable tool for students wanting to learn more about music.. This edition moves most of the content of the companion multi-media CD-ROM to the Online Learning Center providing open access for all students to the many activities and video instrument demonstrations. .
Keywords: Music appreciation,Đánh giá âm nhạc